Stilistika Majas dan Citraan Puisi “Sunyi Yang Tak Habis-Habis” Karya Muhammad Asqalani Eneste - Umi Nur Baity; Anis Febriana Sita Hidayati (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Poetry is literary work that has elements figure of speech and strengthen the poetic element. This study to describe of figure of speech and imagery in the poem